Examining the influence of team work factors on team performance for software development in telecommunication industry - Ahmad, Mazida; Abdulmajeed, Vian; Omar, Mazni; Yasin, Azman; Baharom, Fauziah; Mohd, Haslina; Muhd Darus, Norida (Universiti Teknikal Malaysia Melaka, 2016)
A number of projects have failed in software industry due to exceeding budget and schedule. The main reason for most project failure is poor performance of their development team, in which the team performance is affected by a number of factors.The main objective of this study is to identify the factors that have significant effect on the performance of the software development team.A set of questionnaire has been distributed to a sample of software developers in telecommunication industries in Iraq and Kurdistan Region Government (KRG) using stratified sampling technique.The analysis of the data was carried out using Structural Equation Modeling (SEM) to examine the relationship between the identified factors and the performance on software development team.The results prove that coordination of expertise; communication and mutual support positively affect the performance of software development team.